Stigmatizing attitudes toward Internet gaming disorder, Problematic smartphone use and Problematic social networking site use: An experimental vignette study. (June 2023) - Casale, Silvia; Boursier, Valentina; Musicò, Alessia; Ghinassi, Simon; Cigolini, Gemma; Petrucci, Elisabetta; Gioia, Francesca
Highlights: An experimental within-group vignette study design was implemented. Stigmatizing attitudes differ across IGD, PSU and PSNSU. IGD was seen as more serious and less understandable than both PSU and PSNU. Anger, sadness and desired social distance were significantly stronger toward IGD. PSNSU was attributed to vanity and blamed more than IGD and PSU. Abstract: Public stigma on substance and gambling disorders have been well documented. Negative effects of stigma include shame, embarrassment, fear being judged and the determent of help-seeking behaviors among stigmatized individuals. Less is known about the public perception toward Internet gaming disorder (IGD) and other widespread problematic behaviors that share some characteristics with established behavioral addictions, such as Problematic smartphone use (PSU) and Problematic social networking sites use (PSNSU). The purpose of this study is to compare the public perception of problematic Internet gamers, problematic smartphone users and problematic social networking sites users using an experimental within-group vignette study design. A sample of 280 adults (F = 72.1%; M age = 32.84, SD = 13.85) was recruited and completed the study online. Participants were presented with male OR female vignettes (i.e. the gender of the target in the vignette was randomized) describing an individual with IGD, PSU, and PSNSU. A repeated-measures ANOVA followed by post hoc tests using Bonferroni's correction was used. IGD was seen as more serious, more noticeable, and less understandable than both PSU and PSNU. Moreover, participants' emotional reaction (e.g., anger and sadness) and desired social distance were significantly stronger toward IGD. However, vanity attributions were higher for individuals with PSNSU, which were also more blamed compared to both IGD and PSU. PSU was seen as more controllable than both IGD and PSNSU. The results, taken together, suggest that IGD is perceived as more inherently problematic, but PSNSU also seem to deserve scientific attention as individuals showing symptoms of PSNSU are blamed more than problematic Internet gamers. Our findings provide initial information that can be used when developing interventions to impact stigma toward technological addictions.